The relationship between LH and thyroid volume in patients with PCOS - Cakir Evrim; Sahin Mustafa; Topaloglu Oya; Colak Nujen; Karbek Basak; Gungunes Askin; Arslan Muyesser; Unsal Ilknur; Tutal Esra; Ucan Bekir; Delibasi Tuncay (BMC, 2012)
Abstract Background Thyroid volume (TV) has been found to be associated with age, anthropometry, smoking, iodine status and hyperinsulinemia. Hyperinsulinemia is frequent finding in patients with PCOS and has associations with TV. However, the TV has been evaluated only a few studies in patients with PCOS. Therefore, the aim of this study was to evaluate the biochemical and hormonal variables in patients with PCOS comparing with the controls and their relationships between TV. Methods This was a case-control study conducted in a training and research hospital. The study population consisted of 47 reproductive-age PCOS women and 30 control subjects. We evaluated anthropometric, biochemical and hormonal parameters as well as thyroid volume in PCOS patients and controls. Insulin resistance was calculated using the homeostasis model assessment insulin resistance index (HOMA-IR). Results Mean age, BMI, thyroid stimulant hormone (TSH) levels and TV were similar between groups (p<0.05). The HOMA-IR and free T4 levels were higher in patients with PCOS. However, hyperinsulinemia and insulin resistance were not found to be associated with TV. Thyroid volume was positively correlated with the LH and anti TPO levels. The participants were divided into 2 groups according to HOMA-IR levels. The mean TV measurement was higher in group with higher HOMA-IR levels, but the difference was not significant in young age PCOS patients. Conclusion In early age PCOS patients it was observed that insulin resistance had no effect on TV. In this case, anti TPO and LH have dominant effect on TV. Chronic stimulation with LH and insulin may lead to increase in TV in later stages of the PCOS diseases.